The impact of overdiagnosis on thyroid cancer epidemic in Italy, 1998–2012. (May 2018) - ; Fedeli, Ugo; Varvarà, Massimo; Ravaioli, Alessandra; Pennelli, GianMaria; Valla, Katia; Cusimano, Rosanna; Gasparotti, Cinzia; Taborelli, Martina; Iannelli, Arturo; Leite, Silvia; Manneschi, Gianfranco; et al.
Abstract: Aims: In Italy, incidence rates of thyroid cancer (TC) are among the highest worldwide with substantial intracountry heterogeneity. The aim of the study was to examine time trends of TC incidence in Italy and to estimate the proportion of TC cases potentially attributable to overdiagnosis. Methods: Data on TC cases reported to Italian cancer registries during 1998–2012 aged <85 years were included. Age-standardised incidence rates (ASR) were computed by sex, period, and histology. TC overdiagnosis was estimated by sex, period, age, and Italian region. Results: In Italy between 1998–2002 and 2008–2012, TC ASR increased of 74% in women (from 16.2 to 28.2/100, 000) and of 90% in men (from 5.3 to 10.1/100, 000). ASR increases were nearly exclusively due to papillary TC (+91% in women, +120% in men). In both sexes, more than three-fold differences emerged between regions with highest and lowest ASR. Among TC cases diagnosed in 1998–2012 in Italy, we estimated that overdiagnosis accounted for 75% of cases in women and 63% in men and increased over the study period leading to overdiagnosis of 79% in women and 67% in men in 2008–2012. Notably, overdiagnosis was over 80% among women aged <55 years, and substantial variations were documented across Italian regions, in both genders. Conclusion(s): Incidence rates of TC are steadily increasing in Italy and largely due to overdiagnosis. These findings call for an update of thyroid gland examination practices in the asymptomatic general population, at national and regional levels. Highlights: Incidence rates of thyroid cancer (TC) in Italy are among the highest worldwide. Cancer data were collected from Italian cancer registries for the period 1998–2012, and time trends were analysed. Large increasing heterogeneity of TC incidence rates was observed across regions and areas in Italy. We used a previously developed method to estimate overdiagnosis of TC. The steady increases of TC incidence in Italy are largely due to overdiagnosis.